Biochemical and behavioural alterations induced by arsenic and temperature in Hediste diversicolor of different ages - Valente, Pedro Guilherme Martins (2022)
Chemicals become essential elements to modern society. However, those chemicals are harmful to our planet. Metalloids have natural and anthropogenic sources causing environmental decay of natural conditions, especially those not required for metabolic activity, and can be toxic even at low concentrations due to bioaccumulation of the inhabiting organisms. Due to their proximity to the terrestrial environment, coastal systems are direct recipients of industrial and municipal waste and often serve as sinks for contaminants, as metalloids. Arsenic is a toxic metalloid with natural sources however, its concentration increasing in the marine environment is mainly due to human activity, like fertilizer industry and mining activity. Associated with these environmental stressors are climate changes, as global warming, that are expected to alter metalloids toxicity. Global warming is a worldwide threat, improving physical and biochemical changes on water and impacts on marine ecosystems. The majority of the studies with marine invertebrates focused on the effects of metalloids on adult or larvae organisms, not taking into account how growing stages may be affected by contamination and temperature rise. Polychaetes are key species in marine environments, as they inhabit and play vital roles in helping to boost species biomass and richness and contributes to the food chain and sediment mobilization for cycle of nutrients and contaminants. Due to the lack of information about arsenic and temperature rise on marine invertebrates from different ages, this dissertation aimed to study the effects of temperature increase and arsenic contamination on the polychaete Hediste diversicolor in different stages of growing. For this, organisms with three different sizes 1-2.5cm (small, 3 months), 3-5cm (medium, 5 months) and 6-9cm (large, 7 months) were selected. Organisms of each size were exposed for 28 days to arsenic (0.0, 0.05, 0.25 mg/L, at 16 and 21 ºC. Feeding activity and biochemical responses – neurotransmission, indicators of cell damage, antioxidant and biotransformation enzymes and metabolic capacity, were evaluated. Overall, the results demonstrated that temperature rise combined with As have higher impacts on feeding activity and biochemical endpoints at different ages. Small size organisms have their antioxidant enzymes increased, avoiding lipid damage. However, large size organisms are the most affected class due to SOD inhibition, that did not prevent protein damage. oxidative damage was observed on small and large size organisms exposed at As and 21ºC, demonstrating higher sensibility to the combination of temperature rise and As. The observed alterations in polychaetes behaviour may have ecological consequences, affecting the cycle of nutrients, sediment oxygenation and therefore organisms that depend on the bioturbation of this polychaete. The data obtained in this dissertation demonstrated that different stages of growing of the studied species responded differently to As and temperature rise exposure, highlighting the need of further studies aiming to assess potential effects of environmental changes at different class ages.